Diversity and Inclusion in Higher Education and Societal Contexts International and Interdisciplinary Approaches (Springer International Publishing, 2018)
Groundbreaking in its international, interdisciplinary, and multi-professional approach to diversity and inclusion in higher education, this volume puts theory in conversation with practice, articulates problems, and suggests deep-structured strategies from multiple perspectives including performed art, education, dis/ability studies, institutional as well as government policy, health humanities, history, jurisprudence, psychology, race and ethnicity studies, and semiotic theory. The authors-originating from Austria, Germany, Luxembourg, Trinidad, Turkey, and the US- invite readers to join the conversation and sustain the work.